Improving medical students’ learning strategies, management of workload and wellbeing: a mixed methods case study in undergraduate medical education - Christopher-James Harvey; Kathleen E. Leedham-Green; Cristina Koppel; Arti Maini; Susan F. Smith; Mary J. Morrell; Michael Emerson (BMC Medical Education)
Abstract Background The transition from secondary education to university challenges students’ learning strategies and academic performance, especially in self-directed, problem-based environments like medical school. Passive study methods often fail, while evidence-based strategies like retrieval practice, active learning, and growth mindset foster success. We evaluate a novel academic support programme (Academic Tutoring- (AT)) to enhance study skills, feedback use, and self-directed learning. Methods We developed and implemented AT for 1st year medical students, informed by the psychology of learning and behaviour change, AT aimed to support the development of self-efficacy and effective learning strategies during the transition into university. The programme involved meeting an Academic Tutor one-to-one once per term, and also as a group once per term. Academic Tutors engaged students in learner-centred conversations on study skills and professional development plus their wellbeing and welfare. A Likert questionnaire was designed to measure students’ responses to the experiences and perceived outcomes of AT. We also measured self-efficacy and mindset. Qualitative data was gathered through open-ended response items. Demographic and socioeconomic data was also gathered. Results AT positively impacted time-management and learning strategies. ‘Learning from successes and failures’ and ‘thinking how to achieve goals’ were associated with a growth mindset. All outcome measures were associated with self-efficacy. We noted that students from a widening participation (WP) background tended to show higher growth mindset relative to those from a non-WP background (r = -0.223, p = 0.08) and female students reported higher engagement with the programme (r-0.294, p < 0.001). Students reported changes in behaviours and attitudes, and improved wellbeing. Conclusions Providing medical students with the tools to change their approach to work and revision can improve subjective reports of time management, implementation of successful learning strategies and wellbeing. Successful outcomes were associated with self-efficacy and mindset. These are modifiable constructs, and this work suggests that focussing conversations on self-efficacy and mindset may be beneficial for supporting positive behaviour change.